2008
DOI: 10.1021/la704004m
|View full text |Cite
|
Sign up to set email alerts
|

An Example of How to Use AOT Reverse Micelle Interfaces to Control a Photoinduced Intramolecular Charge-Transfer Process

Abstract: 6-Propionyl-2-(N,N-dimethyl)aminonaphtahalene, PRODAN, is widely used as a fluorescent molecular probe due to its significant Stokes shift in polar solvents. It is an aromatic compound with intramolecular charge-transfer (ICT) states which can be particularly useful as sensors. In this work, we performed absorption, steady-state, time-resolved fluorescence (TRES), and time-resolved area normalized emission (TRANES) spectroscopies on PRODAN dissolved in nonaqueous reverse micelles. The reverse micelles are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 73 publications
8
65
0
Order By: Relevance
“…The molecular probe located in the nonpolar organic solvent always emits from a locally excited (LE) state whereas PRODAN located at the RM interface can emit from LE or ICT or both states (dual fluorescence) at room temperature depending on the AOT RM interface properties (see Scheme 2). [24,25] Furthermore, for PRODAN molecules located at the RM interfaces the results are consistent with the emission of the probe located in a single place within the AOT RM interface from two different excited states rather than from the emission of one excited state of the probe located in a different microenvironment: the interface and the water pool. [24,25] Moreover, we have shown the possibility of switching the state from where PRODAN emits by changing the properties of the AOT RM interfaces.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The molecular probe located in the nonpolar organic solvent always emits from a locally excited (LE) state whereas PRODAN located at the RM interface can emit from LE or ICT or both states (dual fluorescence) at room temperature depending on the AOT RM interface properties (see Scheme 2). [24,25] Furthermore, for PRODAN molecules located at the RM interfaces the results are consistent with the emission of the probe located in a single place within the AOT RM interface from two different excited states rather than from the emission of one excited state of the probe located in a different microenvironment: the interface and the water pool. [24,25] Moreover, we have shown the possibility of switching the state from where PRODAN emits by changing the properties of the AOT RM interfaces.…”
Section: Introductionsupporting
confidence: 82%
“…It is an aromatic compound with intramolecular chargetransfer (ICT) states, and can be particularly useful as a sensor for different kinds of media such as RMs and other membrane mimickers. [24][25][26][27][28][29][30][31][32][33][34][35][36] It is a fluorescent probe that exhibits strong shifts in the absorption and emission spectra on varying the environment. The probe emits an intense, single, broad fluorescence band, strongly red-shifted upon increasing the polarity-polarizability (p*) and the hydrogen-donor ability (a) of the media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, [28] we demonstrated that the emission state of the molecular probe 6-propionyl-2-dimethyl amino naphthalene (PRODAN) can be switched from the local exited to the intramolecular charge-transfer state or can take place from both states (dual fluorescence) by choosing the right AOT nonaqueous reverse-micelle interface. This is very interesting because it is not trivial that the emission states of molecular probes can be controlled at room temperature, and it seems that AOT reverse micelles can do it.…”
Section: [Water]/a C H T U N G T R E N N U N G [Aot] = 10 (Aqueous) Wmentioning
confidence: 98%
“…To do this, we used different approaches: i) invasive techniques, such as absorption and emission spectroscopy of different molecular probes dissolved in different nonaqueous reverse micelles media, [16,17,19,28,29] and ii) noninvasive techniques, such as FTIR and 1 H NMR spectroscopy, [18,20,25] where the main effort was focused on the interpretation of the spectra of different polar solvents encapsulated inside reverse micelles to gain insights into their structure and the existence or not of a polar solvent pool. Thus, we have followed how the n OD or the n ND bands for EG, GY, PG, and FA change as the W S ratio increases.…”
Section: [Water]/a C H T U N G T R E N N U N G [Aot] = 10 (Aqueous) Wmentioning
confidence: 99%